An efficient synthesis of 2-(4-(benzyloxy)phenyl)-N, N-dimethylacetamide substantially free from impurities – Synthesis & characterization of novel impurities - Sachin Sonavane; Sachin Mokal; Shubham Wadekar; Satish Wakchaure; Sharayu Deshmukh (Results in Chemistry, 2021)
An improved process developed for the 2-(4-(Benzyloxy)phenyl)-N, N-dimethylacetamide (BPA) which is key starting material for the synthesis of drug O-desmethylvenlafaxine succinate and asperphenamate was described to eliminate the impurities which will be formed during the process. The best reaction conditions were identified by evaluating the impurity profile and their formation during the synthesis. The optimization of the process was made to control the impurities which was one of the critical parameters in the synthesis of BPA. Both the novel impurities formed during the synthesis were identified, synthesized and characterized.